Case report: Endoscopic full-thickness resection of gastric metastatic tumor from renal cell carcinoma - Yan, Xiaochen; Liu, Lina; Wang, Wenhao; Liu, Chunyan; Cui, Zhenqin (Frontiers in Oncology, 2024)
Renal cell carcinoma (RCC) is a common malignant kidney tumor; however, gastric metastasis is rare. We report the case of an 82-year-old male patient who developed gastric metastasis 12 years after an initial diagnosis of RCC. The patient underwent endoscopic full-thickness resection (EFTR), and the gastric metastatic focus was successfully removed. Postoperative pathology and immunohistochemistry showed that the gastric metastasis originated from RCC. Although gastric metastasis of RCC is rare, it should be suspected in patients with a history of RCC or gastrointestinal symptoms. EFTR is associated with reduced trauma and greater retention of gastric tissue and function. It is a more appropriate choice than surgical resection; however, it requires more endoscopists.